The Effect Of Condensate Water On The Performance Of Automotive Air Conditioning System Under Difference Evaporator Air Inlet Temperature - Sukri, Mohamad Firdaus; Lokman, Rusmiati; Muhajir, Asjufri; Muhamad Damanhuri, Amir Abdullah; Wasbari, Faizil; Sumeru, Kasni (Universiti Malaysia Perlis, 2020)
This paper experimentally investigates the effect of condensate water on the performance of automotive air conditioning (AAC) system under difference evaporator air inlet temperature. An experimental test rig was fabricated using the actual component of AAC system used for Proton Wira passenger car. During experimental work, the volume flow rate of condensate water was manipulated at 0, 140 and 340 ml/min. The evaporator air inlet temperature was also varied at 28, 32 and 36°C. The other parameters of compressor speed, condensate water temperature and condenser air inlet temperature were kept constant at 1550 rpm, 29 ± 1°C and 32 ± 1°C, respectively. The study showed that the coefficient of performance (COP) of the AAC system increases when the volume flow rate of condensate water increased from 0 to 140 ml/min. It was due to a dominant decrease in compressor work, as compared to the drop in cooling capacity. In addition, the highest increment in COP occurred at evaporator air inlet temperature of 36°C (9.8%), followed by evaporator air inlet temperature of 28°C (2.8%) and 32°C (0.4%). The highest COP is 3.66, occurred at evaporator air inlet temperature of 32°C and volume flow rate of condensate water of around 140 ml/min